Dynamics, experiences and aspirations of flea market traders in Gweru - Mlambo, Sephath (Midlands State University, 2019)
The flea markets in the central business district of Gweru are part of a widespread form of informal market activity occurring in many countries and operating at various stages of economic development. This study focused on regulated flea market activities housed in premises run by the Gweru City Council or owned by private individuals. The main units of interest were the traders themselves. This focus on the traders themselves allowed for the characterisation of flea market trading processes as informal entrepreneurial business operations. The literature portrayed informal flea markets in several economies as business activities in flux. Some forty traders out of thousands operating in Gweru central business district were sampled using nonprobability methods. Unstructured interviews were conducted until saturation was achieved. The interviews were subsequently transcribed to aid analysis which in turn relied on NVivo 11, a computer software for analysing qualitative data. For this situated study, grounded theory was chosen to allow for systematic analysis leading to the production of a conceptual framework concerning the traders themselves and the businesses they were involved in. The resulting framework was represented in a core category labelled entrepreneurial compass. This core category and its representative typologies formed important pillars for recommendations affecting the crafting of public policy concerning informal flea market trading. The insights that emerged from the study were, however, conditioned upon the localised nature of the study in the confinement of Gweru CBD in central Zimbabwe.